The Phenomenology of Earnings Management within the Confines of Agency Theory - Palliam, Ralph (International journal of value-based management, 2003)
Agents' selective and acceptable reporting of economic events by different accounting systems, compounded by alternative accounting methods and estimates, make financial statements an approximation of economic reality. The tendency to delay accounting recognition of some transactions suggests that financial statements lag behind reality. The difference between reality and imaginary is often referred to as the agency problem. An essential characteristic of this problem is risk attitudes of principals (shareholders) and agents (management). Shareholders are considered risk neutral in their preferences for individual firms. They are in a position to diversify their shareholdings across multiple firms. Agents on the other hand have security and income that are inextricably linked to one firm. It would not be surprising to find agents exhibiting risk aversion in decisions regarding the firm. Immediately one's attention is drawn to the opportunity costs that arise for the risk-neutral shareholders who prefer that agents maximize their returns. The risk differential between agents and principals creates a problem in principal-agent relationship. It is within this framework that supervisory and incentive alignment mechanisms that alter the risk orientation of agents are set up. Powerful incentives act upon agents as they exercise their judgment, particularly when the judgment can trigger a stock market response that will, in turn, affect the firm in numerous ways. The responsibility of agents is to manage earnings. From a principal's perspective not all of the methods used to achieve this goal are equally desirable. Agents can either increase productivity or they can strategically manipulate accounting choices to affect earnings. The latter method need not come with any associated changes in productivity. Consequently, there is misstatement of the financial results and position. The calculus of earnings management is considered within the confines of agents' treatment of risk. Using an Agency Theory framework, this study examines the techniques used by agents to manage and manipulate earnings. The study initially tests the hypothesis whether earnings are really managed. For this purpose two manipulation indices were developed and based upon these indices the phenomenology earnings management was considered.